Six Sigma software quality improvement : success stories from leaders in the high tech industry - Nanda, Vivek, 1977-; Robinson, Jeffrey A. (New York : McGraw-Hill, 2011)
'Proven techniques for improving software and process quality with Six SigmaThis practical, in-depth guide explains how to apply Six Sigma to solve common product and process improvement challenges in the software and IT industry. Six Sigma Software Quality Improvement covers Define, Measure, Analyze, Improve, and Control (DMAIC), Lean Six Sigma, Design for Six Sigma (DFSS), and Define, Measure, Analyze, Design, and Verify (DMADV). Featuring more than 20 success stories from Motorola, IBM, Cisco, Seagate, Xerox, Thomson Reuters, TCS, EMC, Infosys, and Convergys, the book offers first-hand accounts of corporate Six Sigma programs and explains how these companies are successfully leveraging Six Sigma for software process and quality improvement.The success stories reveal how: Motorola minimized business risk before changing business-critical applications TCS improved fraud detection for a global bank Infosys improved software development productivity for a large multinational bank IBM reduced help desk escalations and overhead activities EMC improved development productivity Motorola realized significant cost avoidance by streamlining processes and project documentation Xerox achieved high-speed product development Seagate reduced application downtime and improved availability to 99.99% Cisco successfully reinvented its Six Sigma program Convergys injected Six Sigma into the company's DNA Thomson Reuters' Six Sigma program gathered significant momentum in a short time Six Sigma was successfully applied in many other projects for defect reduction, cycle time reduction, productivity improvement, and more'--
'To date, there have been very few resources that demonstrate how Six Sigma is applicable to the IT industry. Six Sigma Software Quality Improvement bridges that gap by showing Six Sigma in action, with compelling success stories from today's leading IT companies, including Motorola, Honeywell, GE, and American Express. It offers a true roadmap for software quality improvement from those who have been in the trenches and have won the battles handily. IT companies continue to be challenged in overcoming intractable software quality problems and operational complexity while also trying to deliver software as per the agreed scope, schedule, and budget. Six Sigma Software Quality Improvement illustrates how successful IT companies employ Six Sigma to improve their processes using DMAIC (Define, Measure, Analyze, Improve, Control) and DMADV (Define, Measure, Analyze, Design, Verify) and identify and eliminate waste from their processes using Lean Six Sigma. The book also reveals how companies develop new, robust products using Design for Six Sigma (DFSS) concepts'--
Includes bibliographical references and index.
Keywords: Computer software -- Quality control; Computer software industry -- Quality control; Six Sigma (Quality control standard).